STAD TECHNIQUE TO IMPROVE READING COMPREHENSION IN RECOUNT TEXT - Hidayati Amila Soliha; Chandra Fauzi; Yanti Sri Rezeki; Lisa Apriliana (Relawan Jurnal Indonesia, 2023)
Understanding text in English is challenging for EFL learners. The observations and interviews revealed that students lack vocabulary, identify specific information, and determine the main idea of recount text. This study was conducted to improve students' reading comprehension in recount text using the Student Teams Achievement Divisions (STAD) technique. The study employed a mixed-method research design followingtwo cycles of collaborative action research and collected the data using field notes, an observation checklist, and a reading test. The study sample was an intact class of 8th grade comprising 28 students chosen using purposive sampling. Descriptive statistics such as mean score and percentage were used to analyze the data. The findings demonstrated that the student's reading comprehension mean score in Cycle 1 was 61.8, with 35.7% of students categorized as poor, and in Cycle 2, the average score was 82, with only 3.6% insufficient. Depart from the results above, the researchers concluded that students' reading comprehension improved considerably after the intervention using the STAD technique.